HUBUNGAN ANTARA STATUS GRAVIDA DAN USIA IBU DENGAN KEJADIAN EMESIS GRAVIDARUM BULAN JANUARI-AGUSTUS 2017 DI BPM VERONIKA DAN BPM ENDANG SUTIKNO KOTA KEDIRI. - Ira Titisari; Kartika Chandra Suryaningrum; Mika Mediawati (coba, 2019)
In pregnancy, pregnant women have experience with emesis gravidarum about 67.9%. Pregnancy is a natural event. Woman's body will change during pregnancy. Some uncomfortable thing will appear along with physiological changes during pregnancy such as nausea, vomiting, frequent urination, and lower back pain. The most uncomfortable one was nausea and vomiting. Nausea and vomiting were as known as emesis gravidarum. Nausea and vomiting during pregnancy is a common symptom and often occurs in the first trimester of pregnancy. Feelings of nausea occur because of increased levels of the hormone of estrogen and HCG in serum. The purpose of this study is to determine the relationship between gravida status and maternal age with the incidence of emesis gravidarum in January-August 2017 at BPM Veronika and BPM Endang Sutikno Kediri. Methods in this research were an analytical survey with a cross-sectional approach. The population was 120 with a sample of 93 respondents, using simple random sampling technique. The researcher was collecting the data using the recapitulation sheet from January to August 2017. The result of the gravida status that counted with Chi-Square obtained χ2 count value of 6,8 then at the χ2 table at significance level and df 1 is 3,841 so χ2 value > χ2 table. The result of maternal age that counted with Chi-Square obtained a χ2 count of 4,26 then at the χ2 table at a significance level of df 1 is 3,841 so χ2 count > 2 table. It can be concluded that there was a relationship between gravida status and maternal age with the occurrence of emesis gravidarum in January-August 2017 at BPM Veronika and BPM Endang Sutikno Kediri.